Weight stigma and its impact on paediatric care. Issue 1 (February 2019) - Palad, Carl J.; Yarlagadda, Siddharth; Stanford, Fatima Cody
Abstract : Purpose of review: This review aims to evaluate current research findings relevant to weight stigmatization, to acknowledge the deleterious impact it has on the health of the paediatric population and to provide insight to optimize future guidelines for the treatment of individuals with overweight and obesity. Recent findings: Obesity prevalence continues to rise in the USA with estimates in children from ages 2–19 years of 18.5%, an all-time high. With the increase in obesity, there has been a concomitant increase in weight stigma, which affects both youth and general population across varied levels of socioeconomic status and body sizes. Summary: Weight stigma is a contributing phenomenon to the current obesity epidemic, as individuals with stigmatized experiences (weight-based teasing, bullying, victimization) have increased risks for acquiring adverse health outcomes that encompass the physical, behavioural and psychological. Weight stigma can also lead affected individuals to internalize such experiences which decrease their overall quality of life. Sources of stigma may come from peers, family, educators, media, as well as healthcare professionals, as highlighted in this review. Efforts to establish prevention and treatment strategies for weight stigma may generate further traction to help improve global obesity rates. Video abstract: http://links.lww.com/COE/A15 Abstract : Supplemental Digital Content is available in the text